فعالية طرق تدريس النحو العربي لغير الناطقين باللغة العربية في جامعة الشيخ داود الفطاني الإسلامية بجنوب تايلاند - موهئ، رمزي (Ma'had al-Tarbiyyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziah, 2009)
Since human beings are social beings, language has become an important means of communication. Humans use language to communicate with one another in order to understand and achieve their biological and psychological needs in this world. The Arabic language is regarded as one of the ancient languages known as “the collection of Semantic languages” and it is largely used along with the spread of Islam. Understanding Arabic language however requires the comprehensive knowledge of its grammar. Therefore, Arabic Grammar or Arabic Syntax is considered as one of the fundamental requirements for the Arabic Language learners. Its learning requires learner's immense effort and teacher's effective techniques of teaching. One of the essential parts of teaching and learning Arabic Grammar is the teaching method used in delivering knowledge and syntax. The purpose of this study was to investigate and establish the effectiveness of teaching Arabic Grammar to non-Arabic speakers at Syekh Dawud Al-Fatani Islamic University, Southern Thailand as well as prescribing the relationship between the method of teaching grammar and the students' language proficiency. To achieve the above purpose, the researcher chose 106 students from the Department of Arabic Language and Literature at Syekh Dawud Al-Fatani Islamic University, Southern Thailand as respondents. Information was collected by using questionnaires and interviews. The findings show that the methods of teaching Arabic Grammar used in the University are the Grammar-translation method and the deductive method due to their ease of application in the teaching/learning process as well as facilitating effective understanding of Arabic Grammar. These methods are suitable for teaching grammar but not language proficiency. The findings also indicate that the relationship between the effectiveness of methods used and students' language proficiency are positively significant at .001 and at the level .348. It is therefore evident from the findings that learning grammar is very important in enhancing the ability of language proficiency. At the end of this study, the researcher states the suggestions and recommendations to overcome the challenges connected to the teaching methods used in order to improve the methodology of teaching Arabic to non-native speakers of the language in the future.